Perbandingan Aktivitas Antioksidan dan Antikolesterol serta Kandungan Fenolik dan Flavonoid dari Ekstrak Khaya (Khaya anthotheca) - Suryani, Nani; Komalasari, Komalasari; Sulistriyani, Sulistriyani; Rudiana, Tarso; Ernawati, Eneng Elda; Indriatmoko, Dimas Danang; Jayantie, Dhyneu Dwi; Khaerunnisa, Arini (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Hypercholesterolemia is closely related to cardiovascular disease, which can increase the risk of atherosclerosis. Oxidative stress is related to the development of atherosclerosis because it is related to cellular responses triggered by an imbalance between oxidants and reductants in various layers of blood vessel tissue. K. anthotheca has pharmacological benefits as an antileishmaniasis and antimalarial. The purpose of this study was to determine the antioxidant and anticholesterol activity of K. anthotheca bark based on the type of solvent and to determine the phenolic and flavonoid content of the most active extract. The results indicated that ethyl acetate extract had the best antioxidant activity compared to n-hexane and ethanol extracts, with an IC50 value of 47.82 ppm, followed by ethanol extract at 48.46 ppm and n-hexane extract at 101.89. The value of antioxidant activity is directly proportional to the anticholesterol activity, where the ethyl acetate extract has an EC50 value of 20.42 ppm, the ethanol extract 445.58 ppm, and the n-hexane extract 1,073 ppm. The ethyl acetate extract has a phenolic content of 229.765 mgGAE/g extract and a flavonoid content of 7.63 mgQE/g.